Beyond words: the relevance of autonomy-supportive language in university syllabi - Herrera, Dora; Lira-Delcore, Aranza; Lira Luttges, Benjamín (Frontiers in Psychology, 2025)
IntroductionUniversity syllabi are a semester-long working tool through which professors present a thematic content program, precise assessment mechanisms, and establish the activities schedule, among other tasks. Teachers can promote high-quality motivation among students through syllabi. The goal of this research was to replicate a previous study on the impact of syllabus language on student motivation.MethodsTwo studies were conducted. Study 1 aimed to examine, in 126 first- and second-year students in Humanities General Studies, how they perceive a syllabus with an autonomy-supportive “tone” vs. one with a controlling language. Study 2 explored, in 261 students, basic psychological needs (BPN) satisfaction and their affective approach to the course. Additionally, it investigated the type of motivation (autonomous vs. controlled) that students prioritize when selecting the course.ResultsFindings from Study 1 suggest that autonomy-supportive syllabi are perceived as more attractive, fair, and respectful from the student’s perspective. Results from Study 2 indicate that autonomy-supportive syllabi are related to a better perception of the course, greater BPN satisfaction, and autonomous motivation from students, increasing the probability of them choosing that subject.DiscussionIt is concluded that promoting autonomy, even through the written language shared between teachers and students, is important for improving teaching quality.